2012
DOI: 10.5581/1516-8484.20120106
|View full text |Cite
|
Sign up to set email alerts
|

The influence of hydroxyurea on oxidative stress in sickle cell anemia

Abstract: Objective The oxidative stress in 20 sickle cell anemia patients taking hydroxyurea and 13 sickle cell anemia patients who did not take hydroxyurea was compared with a control group of 96 individuals without any hemoglobinopathy. MethodsOxidative stress was assessed by thiobarbituric acid reactive species production, the Trolox-equivalent antioxidant capacity and plasma glutathione levels. ResultsThiobarbituric acid reactive species values were higher in patients without specific medication, followed by pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 28 publications
3
18
0
Order By: Relevance
“…10 HU is suggested to produce direct oxidant and indirect antioxidant effects 30 ; however, there have been contradictory reports regarding the protective role of HU therapy in SCD patients. [23][24][25][26] To examine the possible proactive role of HU treatment on oxidative imbalance in β-thalassemia, we studied oxidative stress biomarkers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 HU is suggested to produce direct oxidant and indirect antioxidant effects 30 ; however, there have been contradictory reports regarding the protective role of HU therapy in SCD patients. [23][24][25][26] To examine the possible proactive role of HU treatment on oxidative imbalance in β-thalassemia, we studied oxidative stress biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Although the underlying mechanisms for the development of oxidative stress in SCD and β-thalassemia are different, 31 the oxidant/antioxidant ratio seems to be more affected in the latter. 14 On the basis of thiobarbituric acid reactive substances (TBARS) and GSH analysis, a few studies reported an antioxidant role of HU in SCD subjects; 23,24 however, investigations on MDA, 25,26 PON1, 26 and vitamin E 26 have suggested that oxidative damage among SCD patients was independent of HU therapy. It was also argued that the observed discrepancy regarding antioxidant effects of HU therapy might be due to the short treatment period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect can probably be at increased Hb F and other actions of HU . The Hb F concentration increase inhibits the polymerization and sickling of Hb S, which attenuates the oxidants production, thus playing the protecting effect against LPO and hemolysis .…”
Section: Discussionmentioning
confidence: 99%
“…In this edition of the Revista Brasileira de Hematologia e Hemoterapia, Torres et al evaluate plasma markers of oxidative stress between SCD patients on and off HU, a topic that has been only lightly investigated previously (14) . In a previous study, the same group showed that comparing SCD patients on chronic transfusion and chelation therapy to SCD patients on HU and chelation therapy, the latter had lower levels of markers of lipid peroxidation (15) .…”
mentioning
confidence: 99%